Analisis Pengaruh Variasi Kecepatan dan Karakteristik Roda Penggiling Terhadap Kapasitas Hasil Penggilingan - Dimas Aryaputra; Arya Mahendra Sakti; Dyah Riandadari; Nurul Ainu Sofi (Universitas Negeri Surabaya, 2026)
Optimizing the processing of agricultural waste, especially peanut hulls, is a significant challenge inincreasing the economic value of food byproducts. This study aims to analyze the performance of a disc millthrough experiments exploring two key mechanical parameters: variations in shaft rotational speed and thegeometric characteristics of the grinding wheel (number of blades). Experiments were conducted using anFFC-15 machine, where the grinding wheel was varied to 2, 3, and 4 blades, combined with variations in shaftrotational speed of 2400, 2600, and 2800 rpm. The results showed a nonlinear phenomenon, namely thatincreasing the number of blades did not always increase efficiency. The 4-blade configuration actually causedair turbulence and flow resistance, thus reducing production capacity, while the 2-blade configurationtriggered the release of many fine particles. The best performance was achieved with a 3-blade configurationat 2800 rpm, which produced the highest grinding capacity of 0.095 kg per minute. This configuration offersthe best balance between impact frequency and material circulation space, thus becoming a technicalrecommendation for improving the efficiency of the husk waste processing machine.